A mini-open transspinous approach for resection of intramedullary spinal cavernous malformations. (December 2018) - Winkler, Ethan A.; Lu, Alex; Rutledge, W. Caleb; Tabani, Halima; Rodriguez Rubio, Roberto; Mummaneni, Praveen V.; Abla, Adib A.
Highlights: Mini-open surgical approaches reduce morbidity with resection of spinal cord pathology. A mini-open transspinous approach is a feasible option for resection of cavernous malformations. Future studies are needed to define the role of mini-open surgery in spinal cord vascular pathology. Abstract: Background and importance: Advances in minimally invasive (MIS) and mini-open surgical approaches have led to reductions in perioperative morbidity without compromising rates of resection of non-degenerative intradural spinal pathologies. Whether these approaches may be adapted for the surgical resection for intramedullary vascular malformations – such as cavernous malformations (CMs) – has yet to be reported. The authors describe a mini-open transspinous approach to resect a ruptured intramedullary CM of the conus medullaris. Clinical Presentation: A 28-year-old man presented with sudden onset of bilateral lower extremity weakness, urinary retention and saddle anesthesia. Magnetic resonance imaging demonstrated a ruptured CM within the conus medullaris with pronounced extralesional hemorrhage. A mini-open transspinous approach with an expandable tubular retractor was successfully applied to facilitate microsurgical resection of the CM and evacuation of the associated hematoma. The patient made a good neurologic recovery, and postoperative imaging confirmed a gross total resection of the CM. Conclusion: A mini-open transspinous approach utilizing an expandable tubular retractor offers feasible less invasive alternative to provide dorsal midline access for the microsurgical resection of intramedullary spinal CMs. Larger case series or future randomized prospective trials are warranted to fully explore suitability of MIS techniques for the surgical management of intradural spinal cord vascular pathologies – such as CMs.